The Effect of Model Problem Solving on Students' Science Process Skills Class VIII SMPN 34 Padang - Riza Elpia Delita; Rahmadhani Fitri; Dezi Handayani; Heffi Alberida (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The problem of research at SMPN 34 Padang is the low level of Science Process Skills of students from the results of previous observations by carrying out tests conducted in class VII SMPN 34 Padang, showing the average science process skills of students is less than 50%. This study aims to look at the effect of the Problem Solving Model on Science Process Skills in Grade VIII students of SMPN 34 Padang. In Indonesia science process skills is very minimal, because in the learning process the teacher still tends to use the lecture model and question and answer method, so the science process skills is not given to students. This type of research is quasi-experimental with research design Control Group Postest Only Design. The population in this study were eighth grade students of SMPN 34 Padang in the academic year 2018/2019. The samples from this study were class VIII6 as the experimental class and VIII7 as the control class. The research instrument used to view the science process skills of students is the Observation Sheet for Student Activities observed by the observer. Based on the results of research on the knowledge competencies of students, the tcount 4.96> t table 1.67 The Science Process Skills Activity of students in the experimental class was higher than the control class. The conclusion of the study was that the application of the Problem Solving Model had a positive effect on the Science Process Skills of Grade VIII students of SMPN 34 Padang.